1990
DOI: 10.3382/ps.0690378
|View full text |Cite
|
Sign up to set email alerts
|

Production and Egg-Quality Responses of White Leghorn Layers to Anticoccidial Agents

Abstract: Two studies were conducted to determine the effects of anticoccidial agents on the production and reproduction of White Leghorns. In Experiment 1, nicarbazin (NCZ) was fed at 0, 20, 50, and 100 ppm. Hen-day egg production, egg weight, the egg-yolk DNC (4-4'-dinitrocarbanilide) level, and egg-yolk mottling were affected by the treatments. When response was evidenced, the relationship between those variables and the level of NCZ was basically linear. Decreased egg production occurred from Days 5 and 6 of the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 8 publications
1
25
1
1
Order By: Relevance
“…The breast muscles of birds in this group were degenerated. Jones et al (1990) did not observe any effect on egg production, egg weight, shell thickness and egg-yolk mottling when SAL was fed at the 60ugg -1 level to White Leghorn layers for 10 days. Shehata et al (1990) observed damage to liver, kidney and lung of fowl fed salinomycin at 120 and 200 ugg" 1 for 14 days.…”
Section: Effect On Productioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The breast muscles of birds in this group were degenerated. Jones et al (1990) did not observe any effect on egg production, egg weight, shell thickness and egg-yolk mottling when SAL was fed at the 60ugg -1 level to White Leghorn layers for 10 days. Shehata et al (1990) observed damage to liver, kidney and lung of fowl fed salinomycin at 120 and 200 ugg" 1 for 14 days.…”
Section: Effect On Productioncontrasting
confidence: 49%
“…The quantifiable limit was around lOngg" 1 . Various detection limits ranging from 25 to ISOngg" 1 have been reported in the literature (Dimenna et al 1986a,b, 1990, Martinez and Shimoda 1986, Tarbin et al 1993, Asukabe et al 1994, Muldoon et al 1995. Recently, Gerhardt et al (1995) lOngg" 1 as the detection and quantifiable limit of salinomycin, respectively, in spiked beef and chicken tissues.…”
Section: Recoveries and Quantifiable Limitsmentioning
confidence: 94%
“…NCZ disrupts the membrane between the egg albumen and yolk, thus compromising embryo development (Jones et al 1990). NCZ is registered in the USA for use with Canada geese (Branta canadensis; Bynum et al 2007) and feral pigeons (Columbia livia; Fagerstone et al 2008) and, in Italy, to control urban populations of feral pigeons (Ferri et al 2009).…”
Section: Other Contraceptivesmentioning
confidence: 99%
“…NCZ is an equimolar complex consisting of 4,4′-dinitrocarbanilide (DNC) and 2-hydroxy-4,6-dimethylpyrimidine (HDP). It has been used as a coccidiostat in broiler chicken feeds since the 1950s (Jones et al 1990). NCZ also reduces egg production and hatchability by compromising the integrity of the egg's vitelline membrane, allowing yolk and albumen to mix (Sherwood et al 1956;Yoder et al 2006a).…”
Section: Introductionmentioning
confidence: 99%